2011
DOI: 10.1016/j.rmed.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin measurements for guiding antibiotic treatment in pediatric pneumonia

Abstract: In order to evaluate the use of an algorithm based on a procalcitonin (PCT) cut-off value as a means of guiding antibiotic therapy, 319 hospitalised children with uncomplicated community-acquired pneumonia (CAP) were randomised 1:1 to be treated on the basis of the algorithm or in accordance with standard guidelines. The children in the PCT group did not receive antibiotics if their PCT level upon admission was <0.25 ng/mL, and those receiving antibiotics from the time of admission were treated until their PCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 32 publications
6
122
0
3
Order By: Relevance
“…An Italian [24] study performed on 319 children (aged 1 month to 14 years; inpatients), used PCT measurements to guide antibiotic treatment choices. The study design implied that all patients were divided into two subgroups: a PCT-guided therapy group, and an evidence-based therapy group.…”
Section: Pct and Antibiotic Treatmentmentioning
confidence: 99%
“…An Italian [24] study performed on 319 children (aged 1 month to 14 years; inpatients), used PCT measurements to guide antibiotic treatment choices. The study design implied that all patients were divided into two subgroups: a PCT-guided therapy group, and an evidence-based therapy group.…”
Section: Pct and Antibiotic Treatmentmentioning
confidence: 99%
“…The study by Bouadma et al [9] found that the prescription of antimicrobials might be shortened by over 2 days, using the evolution of PCT during the course of major septicaemia in adults hospitalised in intensive care units. Similarly, antimicrobial therapy could be shortened by 5 days in the treatment of community-acquired lung infection in children [10]. Our study also showed that the duration of antimicrobial therapy for secondary sepsis in neonates could be shortened by 5 days by using the serum concentrations of PCT.…”
Section: Discussionmentioning
confidence: 51%
“…Consequently, the duration of antimicrobial therapy was shortened by >2 days on the basis of the evolution of serum PCT concentrations, without increases in morbidity and mortality. Similarly, in children, the evolution of PCT enabled a five day shortening of antimicrobial therapy in the treatment of community-acquired lung diseases [10]. The efficacy of PCT-guided decision making on the duration of antibiotic treatment has never been studied in secondary sepsis of the neonate.…”
Section: Introductionmentioning
confidence: 99%
“…Экспресс-тест для определения БГСА дает возмож-ность выявлять пациентов со стрептококковым фарин-готонзиллитом и проводить антибиотикотерапию при-цельно. Упомянутые выше биомаркеры бактериальных инфекций (С-реактивный белок и прокальцитонин) полезны для принятия решения о старте или прекраще-нии антибактериальной терапии, например для диффе-ренциальной диагностики вирусных и бактериальных пневмоний [27]. Однако, необходимы дополнительные исследования, чтобы использовать их в случаях других инфекций, в том числе в качестве надежного маркера безопасной отмены антибиотиков при инфекциях кро-вотока.…”
Section: что еще можно сделать?unclassified